Managing MSME Innovation Performance: Analysis of Knowledge-Oriented Leadership and Knowledge Management Capability - Suroso Suroso; Dewiana Novitasari; Yunianto Agung Nugroho; Gusli Chidir; Masduki Asbari (Universitas Pahlawan Tuanku Tambusai, 2021)
The purpose of this study was to investigate the practice and effect of knowledge-oriented leadership on innovation performance in the MSME industry, by mediating knowledge management capabilities. The Partial Least Square (PLS) approach was used to analyze the data obtained from 170 employees of several MSMEs in Banten. The results obtained indicate that knowledge-oriented leadership has a positive and significant effect on knowledge management capabilities, but has no significant effect on organizational innovation performance. However, knowledge-oriented leadership has a positive and significant impact on organizational innovation performance through knowledge management capabilities. So knowledge management capability functions as a full mediator variable. From a theoretical perspective, the results of this study provide empirical evidence about the positive role of knowledge management capability as an influential factor to improve MSME innovation performance. Meanwhile, from a managerial perspective, the results of this study provide an overview of decision-makers in MSMEs with a better understanding of how to improve knowledge management capabilities and apply appropriate leadership styles in the current knowledge era.